Characterization of the microRNA Expression Profiles in the Goat Kid Liver - Zhao, Xiaodong; Ji, Zhibin; Xuan, Rong; Wang, Aili; Li, Qing; Zhao, Yilin; Chao, Tianle; Wang, Jianmin (Frontiers in Genetics, 2022)
The liver is the largest digestive gland in goat with an important role in the early metabolic function development. MicroRNAs are crucial for regulating the development and metabolism in the goat liver. In this study, we sequenced the miRNAs in the liver tissues of the goat kid to further research their regulation roles in the early liver development. The liver tissues were procured at 5-time points from the Laiwu black goats of 1 day(D1), 2 weeks(W2), 4 weeks(W4), 8 weeks(W8), and 12 weeks(W12) of age, respectively with 5 goats per time point, for a total of 25 goats. Our study identified 214 differential expression miRNAs, and the expression patterns of 15 randomly selected miRNAs were examined among all five age groups. The GO annotation results showed that DE miRNA target genes were significantly enriched in the fatty acid synthase activity, toxin metabolic process, cell surface, and antibiotic metabolic process. The KEGG analysis result was significantly enriched in steroid hormone synthesis and retinol metabolism pathways. Further miRNA-mRNA regulation network analysis reveals 12 DE miRNA with important regulation roles. Overall, the DE miRNAs were mainly involved in liver development, lipid metabolism, toxin metabolism related biological process and pathways. Our results provide new information about the molecular mechanisms and pathways in the goat kid liver development..